Evaluation of Longitudinal Exposure to Tacrolimus as a Risk Factor of Chronic Kidney Disease Occurrence Within the First-year Post-Liver Transplantation. Issue 7 (July 2021) - Maurel, Pauline; Prémaud, Aurélie; Carrier, Paul; Essig, Marie; Barbier, Louise; Rousseau, Annick; Silvain, Christine; Causse, Xavier; Debette-Gratien, Marilyne; Jacques, Jérémie; Marquet, Pierre; Salamé, Ephrem; et al.
Abstract : Background: Renal failure is predictive of mortality in the early postliver-transplantation period and calcineurin inhibitors toxicity is a main challenge. Our aim is to assess the impact of longitudinal tacrolimus exposure (TLE) and other variables on chronic kidney disease (CKD)-free 1-year-survival. Methods: Retrospective data of consecutive patients transplanted between 2011 and 2016 and treated with tacrolimus were collected. TLE and all relevant pre- and post-liver transplantation (LT) predictive factors of CKD were tested and included in a time-to-event model. CKD was defined by repeated estimated glomerular filtration rate (eGFR) values below 60 mL/min/1.73m 2 at least for the last 3 months before M12 post-LT. Results: Data from 180 patients were analyzed. CKD-free survival was 74.5% and was not associated with TLE. Pre-LT acute kidney injury (AKI) and eGFR at 1-month post-LT (eGFRM1 ) <60 mL/min/1.73m 2 were significant predictors of CKD. By distinguishing 2 situations within AKI (ie, with or without hepatorenal syndrome [HRS]), only HRS-AKI remained associated to CKD. HRS-AKI and eGFRM1 <60 mL/min/1.73m 2 increased the risk of CKD (hazard ratio, 2.5; 95% confidence interval, 1.2-4.9; hazard ratio, 4.8; 95% confidence interval, 2.6-8.8, respectively). Conclusions: In our study, TLE, unlike HRS-AKI and eGFRM1, was not predictive of CKD-free survival at 1-year post-LT. Our results once again question the reversibility of HRS-AKI. Abstract : Supplemental Digital Content is available in the text.